2001
DOI: 10.1093/emboj/20.24.6969
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid defines a novel class of HDAC inhibitors inducing differentiation of transformed cells

Abstract: Histone deacetylases (HDACs) play important roles in transcriptional regulation and pathogenesis of cancer. Thus, HDAC inhibitors are candidate drugs for differentiation therapy of cancer. Here, we show that the well-tolerated antiepileptic drug valproic acid is a powerful HDAC inhibitor. Valproic acid relieves HDAC-dependent transcriptional repression and causes hyperacetylation of histones in cultured cells and in vivo. Valproic acid inhibits HDAC activity in vitro, most probably by binding to the catalytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

51
1,376
3
27

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,696 publications
(1,457 citation statements)
references
References 45 publications
(88 reference statements)
51
1,376
3
27
Order By: Relevance
“…Furthermore, in xenograft experiments in mouse, VPA was shown to decrease tumour growth combined with a more differentiated phenotype of the NB cells (Cinatl et al, 1997. The mechanisms behind these effects remained elusive until recent findings showed that VPA is a potent HDAC inhibitor and that induced differentiation of carcinoma and leukaemic cells could be associated to this activity (Gottlicher et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in xenograft experiments in mouse, VPA was shown to decrease tumour growth combined with a more differentiated phenotype of the NB cells (Cinatl et al, 1997. The mechanisms behind these effects remained elusive until recent findings showed that VPA is a potent HDAC inhibitor and that induced differentiation of carcinoma and leukaemic cells could be associated to this activity (Gottlicher et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms behind these effects are still not clear, but might involve the ERK-signalling cascade, cell-cycle regulatory proteins, inhibition of protein kinase C or activation of PPARg (Yuan et al, 2001;Blaheta and Cinatl, 2002;Gurvich et al, 2004). One important finding is however that VPA functions as an HDAC inhibitor, possibly by binding to the catalytic centre of HDACs (Gottlicher et al, 2001). Furthermore, it was shown that VPA induced differentiation of F9 teratocarcinoma and AML cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21 Recent studies demonstrate that glycogen synthase kinase-3 (GSK-3), a serine/threonine kinase consisting of two isoforms and regulating an array of transcription factors, is a direct target of lithium, 23,24 while VPA inhibits histone deacetylase (HDAC), which has a prominent role in the regulation of gene expression. 25,26 Emerging evidence suggests that inhibition of GSK-3 and HDAC are responsible, at least in part, for the neuroprotective effects of lithium and VPA, respectively. 27,28 The present study was undertaken to investigate whether BDNF exon IV-containing mRNA and promoter IV activity are increased by lithium or VPA treatment in rat cortical neurons, and to determine the BDNF promoter region that confers the sensitivity to either drug.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 HDAC has been catalogued into three classes (for a review, see Gray and Ekstrom 5 ). Class I HDACs consist of HDAC 1, 2, 3, and 8, whereas Class II HDACs include HDAC 4, 5, 6, 7, 9, and 10.…”
Section: Introductionmentioning
confidence: 99%